STRUCTURE OF THE PALEOZOIC ALKALINE-ULTRABASIC INTRUSIONS OF THE KOLA PENINSULA BY GRAVIMETRIC DATA - Arzamastsev A.A.; Arzamastseva L.V.; Glaznev V.N.; Raevskii A.B. (My University, 1998)
Study of the deep structure of the Paleozoic carbonatite complexes of the Kola province has been performed using the original 3D density modeling method based on gravity survey data. Analysis of intrusion models from depths of 12-22 km shows that the studied objects represent subvertical cylindrical bodies, massifs with subsurface magmatic chamber and side feeder channel, and bodies being the apical parts of large alkaline-ultrabasic intrusions. It is shown that in the bodies representing the bottom parts of intrusions ultrabasic rocks are most abundant, while the apical parts of the massifs are dominated by carbonatites. The reconstruction of the magmatic-chamber structure suggests that most carbonatite intrusions of the Kola province initially represented a spindle-shaped stock 15-20 km in vertical extension and with a 2:1 chamber height to diameter ratio. Estimation of the erosion level in the Kola part of Fennoscandia has been carried out by comparison of the data on the intrusion shape, location of the magmatic-reservoir bottoms, and matter composition variations in the vertical sections of the magmatic chambers. The results show that for the post-Devonian period, which has passed since the intrusion formation, the above territory was eroded for 4-11 km, with the southeastern part of the region eroded most strongly.
Keywords: Paleozoic; Paleozoic; Палеозой